Two variants in the KIT gene as candidate causative mutations for a dominant white and a white spotting phenotype in the donkey. (27th March 2015) - Haase, B.; Rieder, S.; Leeb, T.
Summary White spotting phenotypes have been intensively studied in horses, and although similar phenotypes occur in the donkey, little is known about the molecular genetics underlying these patterns in donkeys. White spotting in donkeys can range from only a few white areas to almost complete depigmentation and is characterised by a loss of pigmentation usually progressing from a white spot in the hip area. Completely white‐born donkeys are rare, and the phenotype is characterised by the complete absence of pigment resulting in pink skin and a white coat. A dominant mode of inheritance has been demonstrated for spotting in donkeys. Although the mode of inheritance for the completely white phenotype in donkeys is not clear, the phenotype shows similarities to dominant white in horses. As variants in the KIT gene are known to cause a range of white phenotypes in the horse, we investigated the KIT gene as a potential candidate gene for two phenotypes in the donkey, white spotting and white. A mutation analysis of all 21 KIT exons identified a missense variant in exon 4 (c.662A>C; p.Tyr221Ser) present only in a white‐born donkey. A second variant affecting a splice donor site (c.1978+2T>A) was found exclusively in donkeys with white spotting. Both variants were absent in 24 solid‐coloured controls. To the authors' knowledge, this is the first study investigating genetic mechanisms underlying white phenotypes in donkeys. Our results suggest that two independent KIT alleles are probably responsible for white spotting and white in donkeys.